2023
DOI: 10.3390/jpm13091389
|View full text |Cite
|
Sign up to set email alerts
|

The Power of Customized Clear Aligners in Closing Molar Edentulous Spaces: Clinical and Medico-Legal Considerations in a Scoping Review and Case Report

Alessandra Putrino,
Enrico Marinelli,
Simona Zaami

Abstract: Successful closure of edentulous spaces with clear aligners (CAs) is influenced by many factors. CAs are tailored orthodontic devices whose predictability may have relevant medico-legal implications. This study presents a scoping review about missing molar space closure (MMSC) with CAs and a clinical case. This study aims to highlight the feasibility of molar space closure by mesialization with CAs without hybrid supports. Following PRISMA Sc-review guidelines, English-written randomized/non-randomized/observa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
(84 reference statements)
0
1
0
Order By: Relevance
“…With regard to orthodontic splinting, in the selected literature, there does not seem to be a single orientation with respect to the type of method to be used nor with respect to the time of application on the third molars. Therefore, we maintained the methods and duration of application used for the other types of auto-transplanted teeth [ 10 , 13 , 42 , 43 , 44 , 45 , 46 ]. Still, the bone response visible on radiographs confirms the safety of auto-transplantation, for example, in the successful emergency treatment of complications of an oro-antral fistula [ 32 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…With regard to orthodontic splinting, in the selected literature, there does not seem to be a single orientation with respect to the type of method to be used nor with respect to the time of application on the third molars. Therefore, we maintained the methods and duration of application used for the other types of auto-transplanted teeth [ 10 , 13 , 42 , 43 , 44 , 45 , 46 ]. Still, the bone response visible on radiographs confirms the safety of auto-transplantation, for example, in the successful emergency treatment of complications of an oro-antral fistula [ 32 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…From a biomechanical point of view, CAs produce an orthodontic force that moves the teeth thanks to the reversible deformation of the aligner and a certain level of elasticity [105]. The use of transparent aligners to close an extraction site can cause a pronounced inclination of the adjacent teeth, such as the canines, in the case of extraction of the first premolar, and the posterior teeth, towards the extraction space [75,106]. It has been observed that a certain level of computer planning on the transparent masks can prevent unwanted rollovers towards the extraction space during the closure of the space [75,107].…”
Section: Extractionmentioning
confidence: 99%